The movement of gases in longwall coalface wastes liable to spontaneous combustion - Watt, Alan William (1987)
The increasing depth, distance from surface connections and falling quality of coal mined are factors that increase the risk of spontaneous combustion in working areas. The trend towards high capital investment, high output faces significantly raises the economic consequences of spontaneous combustion. Much work has been directed towards methods of identifying the liability of a coal to spontaneously combust under given conditions. The cost of prevention and combat of spontaneous combustion underground is high, however this work is carried out with little knowledge of the likely location of a heating in a coalface waste. This thesis investigates the airflow patterns in a coalface waste, with a view towards improving the use of prevention and combat methods.